The Indissolubility Principle In Saumlaki District Court Decision Number 21 / Pdt.G/2014/PN.Sml - Barzah Latupono; Theresia Nolda Agnes Narwadan; Ferdly Renaldy Lerebulan (Batulis Civil Law Review, 2022)
Marriage within the Catholic church recognizes the indissolubility found in Canon 1141, which explains that Catholic marriages are consummatum, unbreakable marriages, cannot be cut off by any human power and for any reason, other than death. The Catholic church is the only religion that strongly rejects divorce and does not acknowledge the effectiveness of court rulings that dissolve the marriage of Catholic couples. This principle provides a consequence for married couples who are Catholic. Divorce is the only way when marital harmony is no more. The concept of divorce between religious teachings and the idea of national law differs especially from that of national law, for it provides an opportunity for a couple to divorce as long as there isa clear and valid reason for the congregation, while the Catholic faith says that only death can separate, since marriage is the sacrament and involves god in it. The kind of legal research conducted is normatif where the law is conceptually defined as what is written in the law law (law in books) and or the law is conceived as a code or custom by which human behavior is deemed feasible, the case approach (case approach) and the conceptual approach of approach (approach). Revered to this research we can see that the state approves divorce proceedings because the state merely wants to give its citizens legal certainty, since the state's job is to provide comfort and safety to its citizens. While this study sees the indissolubility principle harmonizes with the principle of difficulty divorce, however, it is still rarely found the application of the indissolubility principle in national law, since basically religious and state teachings cannot be harmonized.